Too Good to Be True: Look-Ahead Bias in Empirical Options Research - Duarte, Jefferson; Jones, Christopher S; Khorram, Mehdi; Mo, Haitao; Wang, Junbo L (Review of Financial Studies, 2026)
Numerous trading strategies examined in options research exhibit remarkably high mean returns and Sharpe ratios. We show some of these seemingly “good deals” are due to look-ahead biases. These biases stem from using information unavailable at the portfolio formation time to filter out observations suspected of being noisy or erroneous. Our results suggest that elevated Sharpe ratios may serve as potential indicators of such look-ahead biases. Furthermore, deviating from previous literature findings, we show that illiquidity is not strongly priced in stock options and that only a small set of stock characteristics are in fact associated with option expected returns. (JEL G12, G14, G17)